Not Working : Latina Immigrants, Low-Wage Jobs, and the Failure of Welfare Reform. - Marchevsky, Alejandra (NYU Press, 2006)
Not Working chronicles the devastating effects of the 1996 welfare reform legislation that ended welfare as we know it. For those who now receive public assistance, "work" means pleading with supervisors for full-time hours, juggling ever-changing work schedules, and shuffling between dead-end jobs that leave one physically and psychically exhausted. Through vivid story-telling and pointed analysis, Not Working profiles the day-to-day struggles of Mexican immigrant women in the Los Angeles area, showing the increased vulnerability they face in the welfare office and labor market. The new "work.